Bioorthogonal imaging probe for STING protein in live cell and fixed tissue - Lee, Hyelim; Park, Ju Young; Yoon, Jubeen; Park, Wonjin; Kang, Miso; Lee, Jeehee; Park, Gyubin; Koh, Minseob; Kim, Hyejin; Sohn, Chang Ho; Lee, Sanghee; Kim, Eunha (Sensors and Actuators B: Chemical, 2024)
Stimulator of interferon genes (STING) is an endoplasmic reticulum membrane protein that plays a vital role in innate immunity. In this study, we report a new bioorthogonal chemical probe derived from a previously reported synthetic STING agonist by properly installing a trans-cyclooctene group without perturbation of the efficacy of the ligand. The probe is employed to investigate localization dynamics of STING in live cultured human cells and fixed mouse brain tissues. We showed that an optimized labeling strategy employing the probe and tetrazine-silicon rhodamine fluorophore conjugates in a stepwise manner enables the successful tracking of STING in live cells using fluorescence microscopy. Overall, our bioorthogonal approach using the probe will facilitate in-depth investigations of intricate mechanisms associated with STING.
Keywords: Bioorthogonal fluorescent probe; Click chemistry; Fluorescent imaging; Fluorescent imaging probe; Fluorescent probes; Imaging probe; Live cell; Stimulator of interferon gene; Tetrazine ligation; Tetrazines; Bioorthogonal fluorescent probe; Click chemistry; Fluorescent imaging probe; Stimulator of interferon Gene; Tetrazine ligation